Maintaining, Enhancing and Restoring the Peatlands of Wales: Unearthing the Challenges of Law and Sustainable Land Management. (8th January 2022) - Jenkins, Victoria; Walker, Jonathan
Abstract: Peatlands are essential to environmental imperatives with respect to achieving net zero and nature recovery. Sustainable Peatland Management (SPM) can help to restore, maintain and enhance peatlands to ensure they meet their potential in delivering multiple ecosystem benefits. SPM has attracted a great deal of attention in policy and practice but there has been no attempt to carry out a comprehensive review of the law and governance issues in this context. This article does so with reference to an exemplar of an area of deep peat in the southeast corner of the Brecon Beacons National Park, in Wales. Mapping the boundaries of law and governance here reveals a pressing need to amend these systems to facilitate effective SPM. It also unearths broader challenges regarding the legal frameworks for sustainable land management that will require a more fundamental response.